Why did Wicksell change his mind about the machinery question? - Mauro Boianovsky (EconomiA, 2014)
The article investigates Wicksell's change of mind about the machinery question between 1890 and 1900/1901. Wicksell at first sided with the so-called “compensation theory” that workers are not harmed by the introduction of machinery. In his lecture notes of April 1900, made available here for the first time, Wicksell deployed marginal productivity theory to discuss the effects of labour-saving technical progress, with inconclusive results. Finally, in his published 1901 Lectures and in his 1900 article about marginal productivity, Wicksell claimed that the introduction of machinery increases output and reduces wages. His analysis was based on the demonstration that free competition maximizes output, but not total utility. It is argued that Wicksell's change of mind and his mature formulation of the machinery question result from his critical assessment of the then new concept of Pareto optimality, together with his reinterpretation and rejection of Ricardo's (1821) contention that the introduction of machinery may diminish output and employment. – – O artigo investiga a mudança de opini\~ao de Wicksell sobre a quest\~ao da maquinaria entre 1890 e 1900/1901. Wicksell inicialmente se aliou à “teoria da compensaç\~ao” de que os trabalhadores n\~ao s\~ao prejudicados pela introduç\~ao de maquinaria. Em suas notas de aula de abril de 1900, tornadas disponíveis aqui pela primeira vez, Wicksell empregou a teoria da produtividade marginal para tratar dos efeitos do progresso técnico poupador de trabalho, com resultados inconclusivos. Finalmente, em suas Lectures de 1901, Wicksell argumentou que a introduç\~ao de maquinaria aumenta o produto a diminui salários. Sua análise se baseou na demonstraç\~ao de que a livre concorrência maximiza o produto, mas n\~ao a utilidade total. O artigo mostra que a mudança de opini\~ao de Wicksell e sua formulaç\~ao madura da quest\~ao da maquinaria resultaram de sua avaliaç\~ao crítica do ent\~ao novo conceito de ótimo de Pareto, juntamente com sua reinterpretaç\~ao e rejeiç\~ao do ponto de Ricardo (1821) de que a introduç\~ao de maquinaria pode diminuir produto e emprego.
Keywords: B12; B13; B31; 330; Public Debt; Public Deficit; Interest rate